Evaluation of dental manifestations in X-linked hypophosphatemia using orthopantomography. - Rena Okawa; Misato Takagi; Takashi Nakamoto; Naoya Kakimoto; Kazuhiko Nakano (PLoS ONE)
Background X-linked hypophosphatemia (XLH) is the most common inherited form of rickets. The presence of sequence variations in the phosphate regulating endopeptidase homolog X-linked (PHEX) gene is associated with increased production of fibroblast growth factor 23 (FGF23). This results in renal phosphate wasting and impaired skeletal mineralization. Spontaneous dental abscesses, caused by endodontic infections resulting from hypomineralization of dentin, are a known dental complication of XLH. There is no objective method to evaluate the severity of dentin dysplasia. The purpose of this study was to develop a quantitative method to evaluate dentin dysplasia using orthopantomography that would allow the values in patients with XLH to be compared with the values in healthy participants of the same age. Methods The severity of dentin dysplasia was analyzed by measuring the pulp cavity area of the tooth using orthopantomographic images. The teeth analyzed were mandibular second primary molars and mandibular first permanent molars with complete root formation. Teeth with dental caries, restorations, or root resorption were excluded. Results This retrospective observational study included a total of 200 images of healthy participants (aged 2-15 years) divided into five age groups and 42 images of 17 patients with XLH. There was a significant tendency for the pulp cavity area to decrease with increasing age in primary and permanent teeth. The pulp chambers of patients with XLH were larger than those of healthy participants in primary and permanent teeth. Conclusion We have established a method of using orthopantomography for quantitative assessment of dentin dysplasia in XLH from the primary dentition to the permanent dentition. Evaluating the severity of dentin hypomineralization by this method is useful in the diagnosis of the dental manifestations of XLH. Early diagnosis of XLH enables oral management and leads to prevention of dental abscesses.